Marine migration influences mercury accumulation in anadromous Arctic char ( Salvelinus alpinus ) - Isabel R. Hilgendag; Michael Power; Mehdi M. Aqdam; Christopher W. Lewis; Zoya Martin; Ashley D. Ehrman; Heidi K. Swanson (Journal of Fish Biology, 2026)
Mercury (Hg) is a globally distributed toxic metal present in northern natural environments that biomagnifies in food webs and bioaccumulates in apex predator fish, such as Arctic char ( Salvelinus alpinus )—an iteroparous species with a circumpolar distribution. Arctic char exhibit a variety of life history types, with the migrating, anadromous life‐history type supporting many subsistence and small‐scale commercial fisheries in the Arctic and sub‐Arctic. Despite anadromous Arctic char having generally lower Hg concentrations than non‐anadromous conspecifics, the mechanisms that contribute to significant inter‐individual differences within this life‐history group have not been well investigated. A total of 119 anadromous Arctic char were captured from inner Frobisher Bay on Baffin Island near Iqaluit, Nunavut, in 2018 and 2019, to investigate causes of inter‐individual differences in Hg concentrations in the anadromous life‐history type of Arctic char. As hypothesized, Hg concentrations significantly decreased with increasing marine prey reliance; marine prey reliance—quantified using δ 34 S ratios—explained 93% of the variability in Hg. Arctic char that relied more on marine (vs freshwater) prey had lower Hg concentrations. Delta 34 S ratios and average somatic growth rate (size‐at‐age) were the best predictors of Hg concentrations among the set of biological variables assessed, and both were negatively related to Hg concentrations in common age groups (i.e., ages 9–13). For samples that had migration data available, Hg concentration increased with age‐at‐first migration ( R 2 = 0.32) and decreased with number of marine migrations ( R 2 = 0.57), suggesting that plasticity in life history tactics affects Hg concentrations in anadromous Arctic char. Overall, results indicate that differences in habitat use and feeding environment (i.e., freshwater vs. marine) play a significant role in determining Hg bioaccumulation in anadromous Arctic char.

Influence of inorganic and organic road deicing salts on the mobilization of metals within an agricultural roadside soil - Hasara Samaraweera; Yolanda Susanne Hedberg; Christopher Power (Chemosphere, 2026)

A systematic literature inventory on the interaction between dietary factors and environmental chemical exposures for nervous system health outcomes - Chelsea A. Weitekamp; Caleb Watson; Ellen Hata; Kirstin Hester; Urmila P. Kodavanti; Christopher Lau; David M. Lehmann; Colette N. Miller; Rachel M. Shaffer; Fatima Soliman; Martha Powers; Francesca M. Branch (Food and Chemical Toxicology, 2026)

Hexavalent Chromium Induces Apoptosis and Autophagy in Human Neurons and Astrocytes via MAPK Pathway Activation - Suttinee Phuagkhaopong; Ratchanon Sukprasert; Rapeewan Settacomkul; Dusadee Ospondpant; Kran Suknuntha; Phisit Khemawoot; Christopher Power; Pornpun Vivithanaporn (Biological Trace Element Research, 2026)

Road salt chloride exposure in urban streambeds and links to groundwater – surface water interactions and salt sources - Grant Hodgins; Clare E. Robinson; Christopher Power; James W. Roy (Science of The Total Environment, 2024)

Optimized survey design for the joint use of direct current resistivity and induced polarization: Monitoring of DNAPL source zone evolution at a virtual field site - Siyuan Qiang; Xiaoqing Shi; André Revil; Xueyuan Kang; Christopher Power (Journal of Contaminant Hydrology, 2024)

Monitoring carbon-based remediation of DNAPL-contaminated groundwater via spectral induced polarization - Angelos Almpanis; Lee Slater; Christopher Power (Journal of Environmental Management, 2024)

Complex electrical measurements of waste rock during acid mine drainage generation and release: Kinetic column tests - Difan Su; Angelos Almpanis; Christopher Power (Journal of Environmental Management, 2024)

Characterization of subsurface pathways contributing to freshwater salinization of urban streams using electrical and electromagnetic imaging techniques - Grant Hodgins; Clare E. Robinson; James W. Roy; Christopher Power (Science of The Total Environment, 2023)

Assessing water dynamics and net percolation rates within engineered cover systems for mine waste rock piles: A long-term field monitoring study - Deanna Hersey; Christopher Power (Journal of Hydrology, 2023)

Spectral induced polarization signatures of smoldering remediation enhanced with colloidal activated carbon: An experimental study - Angelos Almpanis; Lee Slater; Jason I. Gerhard; Christopher Power (Journal of Contaminant Hydrology, 2023)

Characterization of DNAPL source zones in clay-sand media via joint inversion of DC resistivity, induced polarization and borehole data - Xueyuan Kang; Christopher Power; Amalia Kokkinaki; André Revil; Jichun Wu; Xiaoqing Shi; Yaping Deng (Journal of Contaminant Hydrology, 2023)

An improved method for computing tidal datums - Karen Palmer; Christopher S. Watson; John R. Hunter; Ben S. Hague; Hannah E. Power (Coastal Engineering, 2023)

Deconstructing heterogeneity of replicative senescence in human mesenchymal stem cells at single cell resolution - Atefeh Taherian Fard; Hannah C. Leeson; Julio Aguado; Giovanni Pietrogrande; Dominique Power; Cecilia Gómez-Inclán; Huiwen Zheng; Christopher B. Nelson; Farhad Soheilmoghaddam; Nick Glass; Malindrie Dharmaratne; Ebony R. Watson; et al. (GeroScience, 2023)
Following prolonged cell division, mesenchymal stem cells enter replicative senescence, a state of permanent cell cycle arrest that constrains the use of this cell type in regenerative medicine applications and that in vivo substantially contributes to organismal ageing. Multiple cellular processes such as telomere dysfunction, DNA damage and oncogene activation are implicated in promoting replicative senescence, but whether mesenchymal stem cells enter different pre-senescent and senescent states has remained unclear. To address this knowledge gap, we subjected serially passaged human ESC-derived mesenchymal stem cells (esMSCs) to single cell profiling and single cell RNA-sequencing during their progressive entry into replicative senescence. We found that esMSC transitioned through newly identified pre-senescent cell states before entering into three different senescent cell states. By deconstructing this heterogeneity and temporally ordering these pre-senescent and senescent esMSC subpopulations into developmental trajectories, we identified markers and predicted drivers of these cell states. Regulatory networks that capture connections between genes at each timepoint demonstrated a loss of connectivity, and specific genes altered their gene expression distributions as cells entered senescence. Collectively, this data reconciles previous observations that identified different senescence programs within an individual cell type and should enable the design of novel senotherapeutic regimes that can overcome in vitro MSC expansion constraints or that can perhaps slow organismal ageing.

Assessing the importance of drainage layers over geomembrane liners within engineered cover systems: Seven years of field monitoring at three mine waste rock piles - Deanna Hersey; Christopher Power (Geotextiles and Geomembranes, 2023)

Stable isotopes and foraging behaviors support the role of antipredator benefits in driving the association between two marine fishes - Christopher R. Haak; Michael Power; Alexander D. M. Wilson; Andy J. Danylchuk (Oecologia, 2023)

Influence of topical capsaicin cream on thermoregulation and perception during acute exercise in the heat - Alejandro M. Rosales; Marie Powers; Matthias J. Walters; Mark L. McGlynn; Christopher W. Collins; Dustin R. Slivka (Journal of Thermal Biology, 2023)

The impacts of a global pandemic on the efficacy and stability of contemporary wildlife conservation: South Africa as a case study - David A. Ehlers Smith; Yvette C. Ehlers Smith; Harriet T. Davies-Mostert; Lindy J. Thompson; Daniel M. Parker; Deon de Villiers; Dean Ricketts; Brent Coverdale; Peter J. Roberts; Christopher Kelly; Duncan N. Macfadyen; Nomthandazo S. Manqele; et al. (Ambio, 2023)
Conservationists speculated on potential benefits to wildlife of lockdown restrictions because of the COVID-19 pandemic but voiced concern that restrictions impeded nature conservation. We assessed the effects of lockdown restrictions on biodiversity conservation in South Africa, a biodiverse country with economic inequality and reliance on wildlife resources. We solicited expert opinion using the IUCN’s Threats Classification Scheme to structure a questionnaire and illustrated responses with individual case studies from government parastatal and non-governmental conservation organisations. The most highly reported threats were biological resource use, residential/commercial developments, invasive species, and human intrusions. The trends reported by 90 survey respondents were supported by case studies using environmental compliance data from parastatal conservation organisations. Lack of tourism revenue and funding were cited as hindrances to conservation. Mechanisms to prevent environmental degradation in the face of global emergencies must be implemented and ‘ring-fenced’ to ensure conservation is not a casualty during future global crises.

Two canonically aerobic foraminifera express distinct peroxisomal and mitochondrial metabolisms - Christopher Powers; Fatma Gomaa; Elizabeth B. Billings; Daniel R. Utter; David J. Beaudoin; Virginia P. Edgcomb; Colleen M. Hansel; Scott D. Wankel; Helena L. Filipsson; Ying Zhang; Joan M. Bernhard (Frontiers in Marine Science, 2022)
Certain benthic foraminifera thrive in marine sediments with low or undetectable oxygen. Potential survival avenues used by these supposedly aerobic protists include fermentation and anaerobic respiration, although details on their adaptive mechanisms remain elusive. To better understand the metabolic versatility of foraminifera, we studied two benthic species that thrive in oxygen-depleted marine sediments. Here we detail, via transcriptomics and metatranscriptomics, differential gene expression of Nonionella stella and Bolivina argentea , collected from Santa Barbara Basin, California, USA, in response to varied oxygenation and chemical amendments. Organelle-specific metabolic reconstructions revealed these two species utilize adaptable mitochondrial and peroxisomal metabolism. N. stella , most abundant in anoxia and characterized by lack of food vacuoles and abundance of intracellular lipid droplets, was predicted to couple the putative peroxisomal beta-oxidation and glyoxylate cycle with a versatile electron transport system and a partial TCA cycle. In contrast, B. argentea , most abundant in hypoxia and contains food vacuoles, was predicted to utilize the putative peroxisomal gluconeogenesis and a full TCA cycle but lacks the expression of key beta-oxidation and glyoxylate cycle genes. These metabolic adaptations likely confer ecological success while encountering deoxygenation and expand our understanding of metabolic modifications and interactions between mitochondria and peroxisomes in protists.

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

SGLT2 inhibition attenuates arterial dysfunction and decreases vascular F-actin content and expression of proteins associated with oxidative stress in aged mice - Rogerio N. Soares; Francisco I. Ramirez-Perez; Francisco J. Cabral-Amador; Mariana Morales-Quinones; Christopher A. Foote; Thaysa Ghiarone; Neekun Sharma; Gavin Power; James A. Smith; R. Scott Rector; Luis A. Martinez-Lemus; Jaume Padilla; et al. (GeroScience, 2022)
Aging of the vasculature is characterized by endothelial dysfunction and arterial stiffening, two key events in the pathogenesis of cardiovascular disease (CVD). Treatment with sodium glucose transporter 2 (SGLT2) inhibitors is now known to decrease cardiovascular morbidity and mortality in type 2 diabetes. However, whether SGLT2 inhibition attenuates vascular aging is unknown. We first confirmed in a cohort of adult subjects that aging is associated with impaired endothelial function and increased arterial stiffness and that these two variables are inversely correlated. Next, we investigated whether SGLT2 inhibition with empagliflozin (Empa) ameliorates endothelial dysfunction and reduces arterial stiffness in aged mice with confirmed vascular dysfunction. Specifically, we assessed mesenteric artery endothelial function and stiffness (via flow-mediated dilation and pressure myography mechanical responses, respectively) and aortic stiffness (in vivo via pulse wave velocity and ex vivo via atomic force microscopy) in Empa-treated (14 mg/kg/day for 6 weeks) and control 80-week-old C57BL/6 J male mice. We report that Empa-treated mice exhibited improved mesenteric endothelial function compared with control, in parallel with reduced mesenteric artery and aortic stiffness. Additionally, Empa-treated mice had greater vascular endothelial nitric oxide synthase activation, lower phosphorylated cofilin, and filamentous actin content, with downregulation of pathways involved in production of reactive oxygen species. Our findings demonstrate that Empa improves endothelial function and reduces arterial stiffness in a preclinical model of aging, making SGLT2 inhibition a potential therapeutic alternative to reduce the progression of CVD in older individuals. Graphical abstract

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Relationship Between Time-Weighted Head Impact Exposure on Directional Changes in Diffusion Imaging in Youth Football Players - Suraj K. Puvvada; Elizabeth M. Davenport; James M. Holcomb; Logan E. Miller; Christopher T. Whitlow; Alexander K. Powers; Joseph A. Maldjian; Joel D. Stitzel; Jillian E. Urban (Annals of Biomedical Engineering, 2021)

Brain Strain: Computational Model-Based Metrics for Head Impact Exposure and Injury Correlation - Logan E. Miller; Jillian E. Urban; Elizabeth M. Davenport; Alexander K. Powers; Christopher T. Whitlow; Joseph A. Maldjian; Joel D. Stitzel (Annals of Biomedical Engineering, 2021)

A Marine Biodiversity Observation Network for Genetic Monitoring of Hard-Bottom Communities (ARMS-MBON) - Matthias Obst; Katrina Exter; A. Louise Allcock; Christos Arvanitidis; Alizz Axberg; Maria Bustamante; Ibon Cancio; Diego Carreira-Flores; Eva Chatzinikolaou; Giorgos Chatzigeorgiou; Nathan Chrismas; Melody S. Clark; et al. (Frontiers in Marine Science, 2020)
Marine hard-bottom communities are undergoing severe change under the influence of multiple drivers, notably climate change, extraction of natural resources, pollution and eutrophication, habitat degradation, and invasive species. Monitoring marine biodiversity in such habitats is, however, challenging as it typically involves expensive, non-standardized, and often destructive sampling methods that limit its scalability. Differences in monitoring approaches furthermore hinders inter-comparison among monitoring programs. Here, we announce a Marine Biodiversity Observation Network (MBON) consisting of Autonomous Reef Monitoring Structures (ARMS) with the aim to assess the status and changes in benthic fauna with genomic-based methods, notably DNA metabarcoding, in combination with image-based identifications. This article presents the results of a 30-month pilot phase in which we established an operational and geographically expansive ARMS-MBON. The network currently consists of 20 observatories distributed across European coastal waters and the polar regions, in which 134 ARMS have been deployed to date. Sampling takes place annually, either as short-term deployments during the summer or as long-term deployments starting in spring. The pilot phase was used to establish a common set of standards for field sampling, genetic analysis, data management, and legal compliance, which are presented here. We also tested the potential of ARMS for combining genetic and image-based identification methods in comparative studies of benthic diversity, as well as for detecting non-indigenous species. Results show that ARMS are suitable for monitoring hard-bottom environments as they provide genetic data that can be continuously enriched, re-analyzed, and integrated with conventional data to document benthic community composition and detect non-indigenous species. Finally, we provide guidelines to expand the network and present a sustainability plan as part of the European Marine Biological Resource Centre ( www.embrc.eu ).

Lifetime antiretroviral exposure and neurocognitive impairment in HIV - Precious Amusan; Christopher Power; M. John Gill; Daniela Gomez; Erika Johnson; Leah H. Rubin; Esther Fujiwara (Journal of NeuroVirology, 2020)

Machine learning models reveal neurocognitive impairment type and prevalence are associated with distinct variables in HIV/AIDS - Wei Tu; Patricia A. Chen; Noshin Koenig; Daniela Gomez; Esther Fujiwara; M. John Gill; Linglong Kong; Christopher Power (Journal of NeuroVirology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Island questions: the chronology of the Brochtorff Circle at Xagħra, Gozo, and its significance for the Neolithic sequence on Malta - Caroline Malone; Nathaniel Cutajar; T. Rowan McLaughlin; Bernardette Mercieca-Spiteri; Anthony Pace; Ronika K. Power; Simon Stoddart; Sharon Sultana; Christopher Bronk Ramsey; Elaine Dunbar; Alex Bayliss; Frances Healy; et al. (Archaeological and Anthropological Sciences, 2019)

Bonefish in South Florida: status, threats and research needs - Jacob W. Brownscombe; Andy J. Danylchuk; Aaron J. Adams; Brooke Black; Ross Boucek; Michael Power; Jennifer S. Rehage; Rolando O. Santos; Russ W. Fisher; Bill Horn; Christopher R. Haak; Sean Morton; et al. (Environmental Biology of Fishes, 2019)

Hydrodynamic and isotopic niche differentiation between juveniles of two sympatric cryptic bonefishes, Albula vulpes and Albula goreensis - Christopher R. Haak; Michael Power; Geoffrey W. Cowles; Andy J. Danylchuk (Environmental Biology of Fishes, 2019)

Ontogenetic patterns in resource use dynamics of bonefish (Albula vulpes) in the Bahamas - Karen J. Murchie; Christopher R. Haak; Michael Power; Oliver N. Shipley; Andy J. Danylchuk; Steven J. Cooke (Environmental Biology of Fishes, 2019)

Empiric neurocognitive performance profile discovery and interpretation in HIV infection - Daniela Gomez; Christopher Power; M. John Gill; Noshin Koenig; Roberto Vega; Esther Fujiwara (Journal of NeuroVirology, 2019)

Sarcocystis myopathy in a patient with HIV-AIDS - Dustin Anderson; Nabeela Nathoo; Jian-Qiang Lu; Kinga T. Kowalewska-Grochowska; Christopher Power (Journal of NeuroVirology, 2018)

Performance assessment of a single-layer moisture store-and-release cover system at a mine waste rock pile in a seasonally humid region (Nova Scotia, Canada) - Christopher Power; Murugan Ramasamy; Martin Mkandawire (Environmental Monitoring and Assessment, 2018)

Neurologic disease in feline immunodeficiency virus infection: disease mechanisms and therapeutic interventions for NeuroAIDS - Christopher Power (Journal of NeuroVirology, 2018)

Five-year performance monitoring of a high-density polyethylene (HDPE) cover system at a reclaimed mine waste rock pile in the Sydney Coalfield (Nova Scotia, Canada) - Christopher Power; Murugan Ramasamy; Devin MacAskill; Joseph Shea; Joseph MacPhee; David Mayich; Fred Baechler; Martin Mkandawire (Environmental Science and Pollution Research, 2017)

A neuropathic pain syndrome associated with hantavirus infection - Dustin Anderson; Grayson Beecher; Christopher Power; Lindsay Bridgland; Douglas W. Zochodne (Journal of NeuroVirology, 2017)

Modeling brain lentiviral infections during antiretroviral therapy in AIDS - Weston C. Roda; Michael Y. Li; Michael S. Akinwumi; Eugene L. Asahchop; Benjamin B. Gelman; Kenneth W. Witwer; Christopher Power (Journal of NeuroVirology, 2017)

HIV-1 Viral Protein R Activates NLRP3 Inflammasome in Microglia: implications for HIV-1 Associated Neuroinflammation - Manmeet K. Mamik; Elizabeth Hui; William G. Branton; Brienne A. McKenzie; Jesse Chisholm; Eric A. Cohen; Christopher Power (Journal of Neuroimmune Pharmacology, 2017)

A moving target—incorporating knowledge of the spatial ecology of fish into the assessment and management of freshwater fish populations - Steven J. Cooke; Eduardo G. Martins; Daniel P. Struthers; Lee F. G. Gutowsky; Michael Power; Susan E. Doka; John M. Dettmers; David A. Crook; Martyn C. Lucas; Christopher M. Holbrook; Charles C. Krueger (Environmental Monitoring and Assessment, 2016)

Metagenetic analysis of patterns of distribution and diversity of marine meiobenthic eukaryotes - Vera G. Fonseca; Gary R. Carvalho; Ben Nichols; Christopher Quince; Harriet F. Johnson; Simon P. Neill; John D. Lambshead; W. Kelley Thomas; Deborah M. Power; Simon Creer (Global Ecology and Biogeography, 2014)
Aim Meiofaunal communities that inhabit the marine benthos offer unique opportunities to simultaneously study the macroecology of numerous phyla that exhibit different life‐history strategies. Here, we ask: (1) if the macroecology of meiobenthic communities is explained mainly by dispersal constraints or by environmental conditions; and (2) if levels of meiofaunal diversity surpass existing estimates based on morphological taxonomy. Location UK and mainland European coast. Methods Next‐generation sequencing techniques ( NGS ; R oche 454 FLX platform) using 18S nuclear small subunit ribosomal DNA ( rDNA ) gene. Pyrosequences were analysed using A mplicon N oise followed by chimera removal using P erseus . Results Rarefaction curves revealed that sampling saturation was only reached at 15% of sites, highlighting that the bulk of meiofaunal diversity is yet to be discovered. Overall, 1353 OTU s were recovered and assigned to 23 different phyla. The majority of sampled sites had c. 60–70 unique operational taxonomic units ( OTU s) per site, indicating high levels of beta diversity. The environmental parameters that best explained community structure were seawater temperature, geographical distance and sediment size, but most of the variability ( R 2 = 70%–80%) remains unexplained. Main conclusions High percentages of endemic OTU s suggest that meiobenthic community composition is partly niche‐driven, as observed in larger organisms, but also shares macroecological features of microorganisms by showing high levels of cosmopolitanism (albeit on a much smaller scale). Meiobenthic communities exhibited patterns of isolation by distance as well as associations between niche, latitude and temperature, indicating that meiobenthic communities result from a combination of niche assembly and dispersal processes. Conversely, isolation‐by‐distance patterns were not identified in the featured protists, suggesting that animals and protists adhere to radically different macroecological processes, linked to life‐history strategies.

The potential for indirect effects between co‐flowering plants via shared pollinators depends on resource abundance, accessibility and relatedness - Luísa Gigante Carvalheiro; Jacobus Christiaan Biesmeijer; Gita Benadi; Jochen Fründ; Martina Stang; Ignasi Bartomeus; Christopher N. Kaiser‐Bunbury; Mathilde Baude; Sofia I. F. Gomes; Vincent Merckx; Katherine C. R. Baldock; Andrew T. D. Bennett; et al. (Ecology Letters, 2014)
Co‐flowering plant species commonly share flower visitors, and thus have the potential to influence each other's pollination. In this study we analysed 750 quantitative plant–pollinator networks from 28 studies representing diverse biomes worldwide. We show that the potential for one plant species to influence another indirectly via shared pollinators was greater for plants whose resources were more abundant (higher floral unit number and nectar sugar content) and more accessible. The potential indirect influence was also stronger between phylogenetically closer plant species and was independent of plant geographic origin (native vs. non‐native). The positive effect of nectar sugar content and phylogenetic proximity was much more accentuated for bees than for other groups. Consequently, the impact of these factors depends on the pollination mode of plants, e.g. bee or fly pollinated. Our findings may help predict which plant species have the greatest importance in the functioning of plant–pollination networks.

Head Impact Exposure in Youth Football: Elementary School Ages 9–12 Years and the Effect of Practice Structure - Bryan R. Cobb; Jillian E. Urban; Elizabeth M. Davenport; Steven Rowson; Stefan M. Duma; Joseph A. Maldjian; Christopher T. Whitlow; Alexander K. Powers; Joel D. Stitzel (Annals of Biomedical Engineering, 2013)

Head Impact Exposure in Youth Football: High School Ages 14 to 18 Years and Cumulative Impact Analysis - Jillian E. Urban; Elizabeth M. Davenport; Adam J. Golman; Joseph A. Maldjian; Christopher T. Whitlow; Alexander K. Powers; Joel D. Stitzel (Annals of Biomedical Engineering, 2013)

Delineating HIV-Associated Neurocognitive Disorders Using Transgenic Models: The Neuropathogenic Actions of Vpr - Christopher Power; Elizabeth Hui; Pornpun Vivithanaporn; Shaona Acharjee; Maria Polyak (Journal of Neuroimmune Pharmacology, 2012)

Forest Management, Engineering, and Operations - Randy Kolka; Matt Powers; John Bradford; Brian Palik; Marty Jurgensen; Dalia Abbas; Tom Gallagher; Stephen Ambagis; Finto Antony; Lewis Jordan; Richard Daniels; Laurie Schimleck; et al. (Journal of Forestry, 2011)
9Forests represent a major global C sink, and forest management strategies that maximize carbon storage offer one avenue for mitigating increases in atmospheric carbon dioxide concentrations. Our understanding of relationships between forest management, productivity, carbon storage, and stand age, however, is limited. We established research plots in a chronosequence of thinned and unmanaged red pine stands in northern Minnesota to study patterns of carbon storage, and the major fluxes that influence carbon sequestration. We completed an inventory of all major C pools across a chronosequence of 57 red pine stands ages 9-306 years on the Chippewa National Forest in the fall of 2009. Results indicate total ecosystem C pools increase as red pine stands age for at least 150 years, and on-site C storage in thinned stands appears similar to unmanaged stands of comparable ages, despite different age-related trends in the live tree and forest floor pools. Thinned stands may have the potential to store more C than unmanaged stands in old age when C removed during harvesting is added into the total ecosystem C pool.

Ungulate Carcasses Perforate Ecological Filters and Create Biogeochemical Hotspots in Forest Herbaceous Layers Allowing Trees a Competitive Advantage - Joseph K. Bump; Christopher R. Webster; John A. Vucetich; Rolf O. Peterson; Joshua M. Shields; Matthew D. Powers (Ecosystems, 2009)

Dual lentivirus infection potentiates neuroinflammation and neurodegeneration: viral copassage enhances neurovirulence - Amir Afkhami-Goli; Amir Afkhami-Goli; Shu-Hong Liu; Amir Afkhami-Goli; Shu-Hong Liu; Yu Zhu; Joseph M Antony; Hosseinali Arab; Christopher Power (Journal of NeuroVirology, 2009)

Brain-derived human immunodeficiency virus-1 Tat exerts differential effects on LTR transactivation and neuroimmune activation - Leonie A Boven; Farshid Noorbakhsh; Gerben Bouma; Ruurd van der Zee; Diana L Vargas; Carlos Pardo; Justin C McArthur; Hans SLM Nottet; Christopher Power (Journal of NeuroVirology, 2007)

NeuroAIDS, Drug Abuse, and Inflammation: Building Collaborative Research Activities - Joan W. Berman; Monica J. Carson; Linda Chang; Brian M. Cox; Howard S. Fox; R. Gilberto Gonzalez; Glen R. Hanson; Kurt F. Hauser; Wen-Zhe Ho; Jau-Shyong Hong; Eugene O. Major; William F. Maragos; et al. (Journal of Neuroimmune Pharmacology, 2006)

Human immunodeficiency virus type 1 genetic diversity in the nervous system: Evolutionary epiphenomenon or disease determinant? - Guido van Marle; Christopher Power (Journal of NeuroVirology, 2005)

Comparative neurovirulence in lentiviral infections: The roles of viral molecular diversity and select proteases - Christopher Power; Kunyan Zhang; Guido van Marle (Journal of NeuroVirology, 2004)

Cloning and expression of an endocellulase gene from a novel streptomycete isolated from an East African soda lake - Pieter Solingen; Daan Meijer; Wilhelmus Kleij; Christopher Barnett; Robertus Bolle; Scott Power; Brian Jones (Extremophiles, 2001)

Induction of heat shock protein 27 by hydroxyurea and its relationship to experimental metastasis - Allen E. Eskenazi; Jennifer Powers; Jan Pinkas; Steffi Oesterreich; Suzanne A. W. Fuqua; Christopher N. Frantz (Clinical & Experimental Metastasis, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)